Income Inequality in the European Union and its Relationship with Economic Growth and Poverty - Moraliyska–Ivanova, Monika (Research Papers, 2021)
The aim of the study is to examine two serious challenges facing the European Union – poverty and social exclusion, on the one hand, and income inequality, on the other. Tasks include: 1) analysis of income inequality indicators at EU level and as variations between Member States; 2) empirical testing of two hypotheses by analyzing the regression relationship between economic growth, poverty and inequality in the EU in the period 2010 – 2019; 3) analysis of key factors for income inequality in the EU. The thesis is that income inequality in the EU is a serious social and economic problem, which is positively affected by economic growth and redistribution. The hypotheses that are tested through the econometric analysis are: a) Positive economic growth in the EU leads to poverty reduction and b) Positive economic growth in the EU leads to reduction of inequality (in the period 2010 – 2019). The methodology includes: comparative analysis, regression analysis, induction and deduction, the Bourguignon method „Growth-inequality-poverty triangle“ (Bourguignon, 2004). Recommendations have been made. The obtained results show that: 1) there are significant variations in the social indicators of poverty and inequality in the EU member states; 2) There is a direct link between economic growth and poverty reduction and income inequality in the EU; 3) There are various factors for income inequality in the EU.
Keywords: Economic growth; Income inequality; Social exclusion; Poverty; European union